2015
DOI: 10.18488/journal.1/2015.5.6/1.6.355.368
|View full text |Cite
|
Sign up to set email alerts
|

The Importance and Performance of a Destination?s Attributes on Senior Tourists? Satisfaction

Abstract: The purpose of this paper is to study the senior travellers' perception on the importance and performance of Penang's tourism attributes. To do so, the effect of the importance and performance of such attributes on senior tourists' overall satisfaction was also investigated. The perception was assessed by applying importance-performance analysis, whereas its effects were evaluated using partial least squares -structural equation modelling. A total of 12 attributes were chosen in order to evaluate the traveller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…IPA, Importance-Performance Analysis, evaluates the satisfaction of consumers by measuring their perception of the importance of service quality and the actual performances of service quality [1,3]. IPA can be used to evaluate government services [4], tourist destination satisfaction [5] and hotel services [6,7]. In recent years, IPA method has been continuously improved by academia, and has been widely used in rural tourism [8], hot spring service [9] and other reception service industry as an ideal satisfaction assessment tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IPA, Importance-Performance Analysis, evaluates the satisfaction of consumers by measuring their perception of the importance of service quality and the actual performances of service quality [1,3]. IPA can be used to evaluate government services [4], tourist destination satisfaction [5] and hotel services [6,7]. In recent years, IPA method has been continuously improved by academia, and has been widely used in rural tourism [8], hot spring service [9] and other reception service industry as an ideal satisfaction assessment tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is not realistic to obtain people's expectations before leaving for a destination, nor it is accurate to assess their expectations on site by asking them to recall what they expected before leaving [31]. Alternatively, much of the research has chosen to measure attribute importance and performance and then examine the extent to which these two measures correlate with the attribute-level satisfaction or overall satisfaction [4,9,45,46]. However, some have used perceived performance or quality of service as a priori to measure satisfaction [9,31], although these constructs are conceptually different [45].…”
Section: Importance Performance and Satisfactionmentioning
confidence: 99%
“…Previous studies have found that both importance and performance have significant effects on overall satisfaction. For example, it is found that both importance and performance significantly and directly contribute to satisfaction; the impact of performance, however, is more significant than importance [4]. Moreover, importance indirectly impacts satisfaction via its impact on performance.…”
Section: Importance Performance and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the empirical literature, numerous scholars (Abooali et al, 2015;Esichaikul, 2012;Johann & Padma, 2016;Lee, 2016) have recently examined seniors' perceptions of destination attributes. Most of these studies have treated the senior travel market as a homogeneous group across generations (Lehto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%